2021
DOI: 10.23960/jep.v10i2.268
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Determinan Ketimpangan Pendapatan Di Provinsi Jawa Barat Tahun 2015-2020

Abstract: This study aims to analyze the factors that influence income inequality in the province of West Java. The data used is in the form of a cross-section of 28 districts or cities in the area of West Java and a time series for a period of 6 years, namely from 2015-2020. This study uses panel data regression analysis using a fixed-effect model and is processed with the help of Eviews 10. The results showed that the Human Development Index had a significant positive effect on income inequality. The population had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Berdasarkan penelitian (Araja et al, 2020) serta dalam (Dias & Indrawati, 2021)mendapati hasil dimana indeks pembangunan manusia terhadap ketimpangan distribusi pendapatan berdampak positif signifikan. Penemuan berbeda ditemukan pada penelitian (Andina et al, 2021) serta (Syamsir & Rahman, 2018) yang menemui hasil negatif serta signifikan pada hubungan antara indeks pembangunan manusia dan ketimpangan distribusi pendapatan.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Berdasarkan penelitian (Araja et al, 2020) serta dalam (Dias & Indrawati, 2021)mendapati hasil dimana indeks pembangunan manusia terhadap ketimpangan distribusi pendapatan berdampak positif signifikan. Penemuan berbeda ditemukan pada penelitian (Andina et al, 2021) serta (Syamsir & Rahman, 2018) yang menemui hasil negatif serta signifikan pada hubungan antara indeks pembangunan manusia dan ketimpangan distribusi pendapatan.…”
Section: Pendahuluanunclassified
“…Dalam temuan (Nadya & Syafri, 2019)tingkat pengangguran terbuka membawa pengaruh negatif serta signifikan sedangkan pada penelitian yang telah dilakukan oleh (Dias & Indrawati, 2021) serta (Hindun et al, 2019) menemui hasil positif yang tidak signifikan pada hubungan antara tingkat pengangguran terbuka dan ketimpangan distribusi pendapatan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Studies by [32]- [34] found that income inequality harms economic development in West Java Province. These studies found that high levels of income inequality in the province result in lower levels of investment, which harms economic growth [27], [35].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between income inequality, economic growth, inflation, and unemployment is complex and varies depending on specific contexts. In West Java Province, policies aimed at reducing income inequality, inflation, and unemployment can have both positive and negative impacts on economic growth [2], [21], [28], [32], [34], [43], [44].…”
Section: Introductionmentioning
confidence: 99%